Institutional reforms and the role of multilateral aid agencies - Sylvanus I. Ikhide (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper reviews the role of the multilateral aid agencies in the delivery of aid. The role of these institutions is as old as the debate on the role of aid in economic development. Aid is effective in a good policy environment. However, effective aid delivery is equally crucial. This is why the need to reform the institutions involved in the process of delivering aid is crucial. Among others, the paper concluded that there is a need for redefining the roles and the establishment of a well articulated network among the various institutions involved in the aid process. More importantly, given the different actors and motives at play in the transfer of resources to recipient countries, the role of a supranational institution to coordinate and give direction is indispensable.
Keywords: F35; G29; 330; foreign aid; institutions; development aid; Entwicklungsorganisation; Entwicklungshilfe